About the training of personnel for teaching the subject of music - Dzvelaia, Tamar (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
The article discusses the importance of the teacher training educational program and the preparation of novice teachers for school life. The article discusses the curriculum of the program and the syllabus of several school courses. In the form of an appendix, a resource for music teachers, a workshop plan, is presented.